2021
DOI: 10.1007/s10584-021-03268-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of stratospheric aerosol injection on drought risk managements over major river basins in Africa

Abstract: Most socio-economic activities in Africa depend on the continent’s river basins, but effectively managing drought risks over the basins in response to climate change remains a big challenge. While studies have shown that the stratospheric aerosol injection (SAI) intervention could mitigate temperature-related climate change impacts over Africa, there is a dearth of information on how the SAI intervention could influence drought characteristics and drought risk managements over the river basins. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…For example, at the end of the time series of the Matam station, SPEI-12 and SPEI-24 indicate a wet period while SPI-12 and SPI-24 indicate a continuation of the drought (Figure 4). The analysis of the SPI and SPEI results supports numerous studies in Senegal [16,17,19,28,36,37] which concluded that there has been a rainfall deficit since the 1970s. Similar results were also obtained by Ali and Lebel (2009) [38] who showed the persistence of drought during the 1970s throughout West Africa, especially the Sahel.…”
Section: Discussionsupporting
confidence: 83%
“…For example, at the end of the time series of the Matam station, SPEI-12 and SPEI-24 indicate a wet period while SPI-12 and SPI-24 indicate a continuation of the drought (Figure 4). The analysis of the SPI and SPEI results supports numerous studies in Senegal [16,17,19,28,36,37] which concluded that there has been a rainfall deficit since the 1970s. Similar results were also obtained by Ali and Lebel (2009) [38] who showed the persistence of drought during the 1970s throughout West Africa, especially the Sahel.…”
Section: Discussionsupporting
confidence: 83%
“…Different regions of Africa have different projections for SPI (rainfall) droughts and SPEI (potential evapotranspiration) droughts under different scenarios of climate change and geoengineering. Abiodun et al (2021) examined projections of climate change using a single climate model, the Community Earth System Model (CESM1) with 20 ensemble members under the RCP 8.5 scenario, and compared this with a scenario of solar geoengineering from the Stratospheric Aerosol Geoengineering Large Ensemble (GLENS) Project. In this experiment the stratospheric injection rate is calculated to maintain the global mean temperature as well as the inter-hemispheric and equatorto-pole near-surface temperatures at the 2020 level until the end of the century while keeping other forcing as in the RCP 8.5 scenario.…”
Section: Discussionmentioning
confidence: 99%
“…To contextualize the analysis of societal outcomes, we reproduce here the results from Abiodun et al (2021), which depict the geographic distribution of changes to SPI and SPEI across Africa under a strong climate change scenario and a specific scenario solar geoengineering that fully offsets global temperature increases due to climate change. When we refer to "solar geoengineering, " we are referring specifically to stratospheric aerosol injection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations